Hibernators, their awakeners and the roles of subsequent authoritative citers - Hu, Xiaojun; Hu, Xiaoyue; Zhang, Yuning; Rousseau, Ronald (Malaysian Journal of Library and Information Science, 2018)
In this contribution we study four examples of hibernators and their citation relations with their awakeners. We, moreover, introduce the notion of authoritative citers, a group of articles that, like the awakener, cite the hibernator and play similar roles as the awakener. Yet, the interplay between the hibernator, the awakener and authoritative citers may differ considerably depending on the case at hand. The results of our study show that authoritative citers play an important role in spreading the knowledge of the hibernator and keeping it in the scientific limelight. This observation provides new insights in the role played by hibernators in scientific evolution.